Trends of school principals towards the academic acceleration of gifted students in primary schools in Kuwait - Al-Rassam, Tahani Falah Abdullah (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify the trends of school principals towards academic acceleration in primary schools in Kuwait and to explain the reasons for not using academic acceleration. The study used the descriptive method and used a tool developed by the researcher. The study sample consisted of 100 managers and managers. (100%) and the statistical processing of data through the SPSS program. The study found that the attitudes of primary school principals in Kuwait towards the academic acceleration of gifted students reached an average of (3.49) of (5) There are several reasons behind the lack of use of academic acceleration in primary schools in the State of Kuwait. It obtained an average of (3.61) from (5) and came to a moderate degree. The study showed that there were statistically significant differences at the level of (P00.05) In the State of Kuwait towards the academic acceleration of gifted students according to (gender and scientific qualification). In light of the results of the study, the researcher presented a number of recommendations to care for the talented and ways to deal with them.